Exposure to air particulate matter with a case study in Guangzhou: Is indoor environment a safe haven in China? - Hu, Yuan-Jie; Bao, Lian-Jun; Huang, Chun-Li; Li, Shao-Meng; Liu, Peter; Zeng, Eddy Y. (ATMOSPHERIC ENVIRONMENT, 2018)
Urban residents spend the majority of time in indoor environments, which, however, may not be a safe haven for staying away from outdoor air pollution, especially in China. To examine this hypothesis, the particle mass concentrations (0.056-18 mu m) and number concentrations (14-660 nm) were simultaneously measured in and outside of three typical urban indoor settings (n = 9), i.e., school, office and residence in Guangzhou, China from October-November 2014 (dry weather season) and June-August 2015 (wet weather season). The indoor and outdoor particle number concentrations were positively correlated with each other at all three sampling settings for both dry and wet weather seasons (r(2) = 0.13-0.65, p < 0.001). The infiltration factors and indoor/outdoor ratios of particles (14-660 nm) were estimated at 0.30-0.75 and 0.85-1.5, respectively, which were comparable to or higher than those (0.12-0.76 and 0.03-1.1) found in cites of other countries under infiltration conditions. Furthermore, the average infiltration factor of fine particle numbers (50-660 nm) in an office was 0.61 during a severe haze episode, indicating that approximately 60% of outdoor particles penetrated indoors. All findings suggested an efficient transport of outdoor particle sources into indoor environment, confirming that exposure of the general public to indoor particles in China should not be overlooked due to effective infiltration of outdoor particles and frequent heavy haze episodes.